Penerapan Pembimbingan dan Pendampingan Tenaga Administrasi dalam Peningkatan Kinerja Sekolah di SMP Negeri 1 Tembuku - Pradnyana, I Putu Eka (Metta : Jurnal Ilmu Multidisiplin, 2022)
Initial observations of the School Administration Staff of SMP Negeri 1 Tembuku show that their performance is still very low. The low performance of School Administration Personnel is due to the lack of appropriate approach used. This makes the implementation of administration in schools not run optimally. To improve the performance of School Administration Personnel, the right approach is needed, namely by guidance and mentoring. The purpose of making this article is to improve the performance of School Administration Personnel in carrying out administrative duties. This research was located at SMP Negeri 1 Tembuku with 11 administrative staff responders. Data is obtained by distributing instruments to respondents, then descriptive analysis is carried out. This research was carried out through two cycles. Each cycle is carried out with several stages, namely: (1) preparation of activity plans, (2) implementation of actions, (3) observation, and (4) analysis and continued with reflection. The results showed that the initial observation of guidance and mentoring was less active, and the response of school administration staff to the principal's explanation was very small so that the average score of school administration staff was 74.55 (grade category C = Sufficient). After the action of cycle I is performed. Through more intensive guidance and mentoring, it led to an increase to an average of 84.32 (grade category B = Good). Results in cycle II increased to an average of 92.95 (grade category A = Very Good). The conclusion is that the implementation of guidance and mentoring can be used as an alternative to improve the performance of School Administration Personnel in carrying out administrative duties.